Trends in hospital admissions and mortality from diabetes mellitus in Rio Grande do Sul: historical series 2000-2020 - Douglas Nunes Stahnke; Camila Nied; Marina Luiza Grudginski de Oliveira; Juvenal Soares Dias da Costa (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To analyze the trends of hospital admissions and deaths from diabetes mellitus in the 18 host municipalities of the 19 regional health coordination offices and in Rio Grande do Sul, 2000-2020. Method: Ecological study with secondary data collected in the Hospital Information System, the Mortality Information System, and the Brazilian Institute of Geography and Statistics, from 2000-2020. Coefficients were standardized using the direct method and Prais-Winsten regression analysis. Results: A downward trend wasfound in the coefficients of hospitalizations for diabetes mellitus in most cities and states. In 2020, for both areas, hospitalizations for diabetes mellitus were below the average of the period. The mortality trend remained stationary in almost all municipalities and in the state. Conclusion: There was evidence of a decrease in hospitalizations and stationary mortality by DM in most municipalities analyzed, possibly due to the policies and actions implemented in the period, despite the aging of the population.